No effect of APOE and PVRL2 on the clinical outcome of multiple sclerosis. - Ramagopalan, S; Deluca, G; Morrison, K; Herrera, B; Dyment, D; Orton, S; Bihoreau, M; Degenhardt, A; Pugliatti, M; Sadovnick, A; Sotgiu, S; Ebers, G (2007)
Multiple sclerosis (MS) is a common inflammatory disease of the central nervous system unsurpassed for its variability in disease outcome. Apolipoprotein E (APOE) is involved in neuronal remodelling and several studies have attempted to examine the effect of APOE on MS disease severity, but its function in modifying the course of MS is controversial. It has been suggested recently that PVRL2, not APOE, is the locus on chromosome 19 which influences clinical outcome of MS. A cohort of sporadic MS cases, taken from opposite extremes of the putative distribution of long-term outcome using the most stringent clinical criteria to date, was used to determine the role of APOE and PVRL2 on MS disease severity. The MS cases selected represent the prognostic best 5% (benign MS) and worst 5% (malignant MS) of cases in terms of clinical outcome assessed by the EDSS. Genotyping the two sets of MS patients (112 benign and 51 malignant) and a replication cohort from Sardinia provided no evidence to suggest that APOE or PVRL2 have any outcome modifying activity. We conclude that APOE and PVRL2 have little or no effect on the clinical outcome of MS.